Experimental Investigation of the Anomalously Low Friction Phenomena in Blocky Rock Systems. (10th October 2020) - Shi, Yehui; Lu, Hao; Deng, Shuxin; Xu, Chenghua; Cheng, Helan
Abstract : Rock masses can be regarded as a blocky rock system. After a disturbance load is applied, the anomalously low friction phenomenon may take place and cause geological disasters. A series of impact experiments on granite blocks were conducted to investigate the anomalously low friction phenomena. Vertical vibration, Fourier frequency spectrum, and horizontal motions were investigated. It can be found that the tensile phases of vertical vibration can reduce the maximum static friction force, namely, the shear strength. The quasi-resonance operating mode of the rock blocks was observed. During the stress wave propagation, the vibration in the loading direction tends to transfer from high frequency to low frequency and the modes of stress wave propagation do not depend on disturbance energies. The observed translational and rotational motions were due to the initial shear force, which is less than the friction force with no disturbance load. Stability of the blocky rock system is very sensitive to the initial stress state. In the subcritical state, friction force reduction can easily break the equilibrium of forces along the contact surface and even a slight disturbance may make the horizontal motions happen, which may lead to geological disasters with great energy release.